Terrestrial orchid conservation in the age of extinction - Swarts, N.; Dixon, Kingsley (Oxford University Press, 2009)
BackgroundConservation through reserves alone is now considered unlikely to achieve protection of plant species necessary to mitigate direct losses of habitat and the pervasive impact of global climate change. Assisted translocation/migration represent new challenges in the face of climate change; species, particularly orchids, will need artificial assistance to migrate from hostile environments, across ecological barriers (alienated lands such as farmlands and built infrastructure) to new climatically buffered sites. The technology and science to underpin assisted migration concepts are in their infancy for plants in general, and orchids, with their high degree of rarity, represent a particularly challenging group for which these principles need to be developed. It is likely that orchids, more than any other plant family, will be in the front-line of species to suffer large-scale extinction events as a result of climate change.ScopeThe South West Australian Floristic Region (SWAFR) is the only global biodiversity hotspot in Australia and represents an ideal test-bed for development of orchid conservation principles. Orchids comprise 6 of all threatened vascular plants in the SWAFR, with 76 out of the 407 species known for the region having a high level of conservation risk. The situation in the SWAFR is a portent of the global crisis in terrestrial orchid conservation, and it is a region where innovative conservation solutions will be required if the impending wave of extinction is to be averted. Major threatening processes are varied, and include land clearance, salinity, burning, weed encroachment, disease and pests. This is compounded by highly specialized pollinators (locally endemic native invertebrates) and, in the most threatened groups such as hammer orchids (Drakaea) and spider orchids (Caladenia), high levels of mycorrhizal specialization. Management and development of effective conservation strategies for SWAFR orchids require a wide range of integrated scientific approaches to mitigate impacts that directly influence ecological traits critical for survival.ConclusionsIn response to threats to orchid species, integrated conservation approaches have been adopted (including ex situ and translocation principles) in the SWAFR with the result that a significant, multidisciplinary approach is under development to facilitate conservation of some of the most threatened taxa and build expertise to carry out assisted migration to new sites. Here the past two decades of orchid conservation research in the SWAFR and the role of research-based approaches for managing effective orchid conservation in a global biodiversity hotspot are reviewed.